PENGEMBANGAN LKS BERBASIS KETERAMPILAN PROSES SAINS (KPS) UNTUK MENINGKATKAN KPS SISWA - Dwi Puspita Sari; Tri Jalmo; Berti Yolida (Universitas Lampung, 2015)
This study aims were to produce worksheets based on science process skills that effectively improve science process skill of students and determine the response of students. Design of the research was research and development. Test was performed on grade VII1 and VII2 student of SMP Pembangunan Kalianda chosen by purposive sampling. Results from this study showed the average N-gain of science process skill students in the experimental class was higher than the control class, thus the aspect of observing, interpreting, grouping, and communicating. In addition, the average of science process skill students increased from worksheet 1 (25.83%), worksheet 2 (75%), and worksheet 3 (83.33%). Worksheet gained by the student assessment criteria of 95% was attractive to very attractive. Thus worksheet based science process skill on material classification of plant was effectively improve students science process skill and very exciting to be used as one of alternative teaching materials for teachers and students.Penelitian bertujuan untuk menghasilkan LKS berbasis KPS yang efektif meningkatkan KPS siswa dan mengetahui tanggapan siswa. Desain penelitian adalah research and development. Uji coba dilakukan pada siswa kelas VII1 dan VII2SMP Pembangunan Kalianda dipilih secara purposive sampling. Hasil penelitian menunjukkan rata-rata N-gain KPS siswa pada kelas eksperimen lebih tinggi dibandingkan kelas kontrol baik aspek mengamati, menginterpretasi, mengelompokkan, dan mengomunikasikan. Selain itu, rata-rata KPS siswa meningkat dari LKS 1 (25.83%), LKS 2 (75%), dan LKS 3 (83.33%). LKS memperoleh penilaian oleh siswa sebesar 95% kriteria menarik hingga sangat menarik. Dengan demikian LKS berbasis KPS pada materi klasifikasi tumbuhan efektif meningkatkan KPS siswa dan sangat menarik untuk digunakan sebagai salah satu bahan ajar alternatif bagi guru dan siswa.Kata kunci: keterampilan proses sains, klasifikasi tumbuhan, lembarkerja siswa (LKS)